2020
DOI: 10.25134/erjee.v8i2.2120
|View full text |Cite
|
Sign up to set email alerts
|

Project-Based Learning in Teaching Writing: The Implementation and Students� Opinion

Abstract: Writing becomes the most challenging skill for the students as it needs more time to develop and tend to raise problem to students. Therefore, project based learning is offered to solve the problems in writing. Some experts believe that project based learning (PBL) can provoke the students to get new knowledge through their own project. This research reports on the implementation of project based learning in teaching writing. The objectives of the research are to know the implementation of project base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…Through this approach, students can build their knowledge and writing skills by engaging in various steps of the project. According to Argawati, & Suryani (2020),Nguyen,(2011, project-based learning provides students with the opportunity to engage in critical thiking, communication, collaboration, and creativity, which are essential skills for effective writing. Project-based learning also promotes motivation and engagement, as students are given the opportunity to explore and apply their knowledge in a meaningful and interesting way.…”
Section: Project Based Learningmentioning
confidence: 99%
“…Through this approach, students can build their knowledge and writing skills by engaging in various steps of the project. According to Argawati, & Suryani (2020),Nguyen,(2011, project-based learning provides students with the opportunity to engage in critical thiking, communication, collaboration, and creativity, which are essential skills for effective writing. Project-based learning also promotes motivation and engagement, as students are given the opportunity to explore and apply their knowledge in a meaningful and interesting way.…”
Section: Project Based Learningmentioning
confidence: 99%
“…In a private university in Indonesia, Ayu's ( 2021) study revealed that text feature walks strategy was effective to help students in higher education deal with their difficulties in critical reading comprehension of textbooks and informational texts. Regarding writing, a study by Argawati and Suryani (2020) showed that university teachers used project-based learning methods to solve students' problems related to writing skills. The study revealed that the method was effective to develop students' active and critical thinking and collaborative learning necessary for writing.…”
Section: Prospects Of Exercising Teacher Agency In Facing Students Le...mentioning
confidence: 99%
“…Moreover, in the PjBL class, students with high creativity were found to be able to produce a better piece of writing compared to those who have a lower one. Furthermore, a study revealed that students were being more active in the class where PjBL is being implemented (Argawati & Suryani, 2020). Besides, it also supports students in producing a good piece of writing.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies show positive results of PjBL implementation (Argawati & Suryani, 2020;Praba̕ et al, 2018;Salsabila, 2018;Soffiany & Purbani, 2020;Wibowo & Aji, 2017). Related to students' low writing creativity and non-suitable learning method, a study has implemented the use of PjBL by asking students to produce a piece of writing in the form of a greeting card (Wibowo & Aji, 2017).…”
Section: Introductionmentioning
confidence: 99%